The Influence Of Service Quality And Trust On The Acceptors Loyalty Of Through Consumer Satisfaction As A Mediation Variable In The National Population And Family Planning Board (Bkkbn) Tanggamus District - M. Khoirul Aulia; Satria Bangsawan; Dorroty RH Pandjaitan (Journal of Social Research, 2024)
Acceptor Loyaltyin research This as variable dependent , whether loyalty consumer after quality services provided by the district BKKBN Tanggamus give impact positive to BKKBN 's performance own research carried out For know service quality, consumer trustin a way Partial influential direct to Acceptor Loyalty, service qualityand consumer trustin a way Partial influential to variable mediation ie satisfaction customers , loyalty consumers , service qualityand trust consumers who are mediated by satisfaction consumer in a way Partial mediate or in a way No direct to Acceptor Loyalty. Research carried out use method perposive random sampling with amount sample of 220 respondents with SEM method using tool analysis namely Amos. Findings empirical results obtained is Service qualityinfluential positive and significant to Acceptor Loyaltyat Regency BKKBN Tanggamus . Consumer trustInfluential positive and significant to Acceptor Loyalty. Service qualityinfluential positive and significant to satisfaction consumer Consumer trustinfluential positive and n significant to papacy customer . Satisfaction consumer influential positive and significant to Acceptor Loyalty. Service qualityinfluential positive and significant to Acceptor Loyaltythrough satisfaction consumer as variable mediation Consumer trustInfluential positive and significant to Acceptor Loyaltythrough satisfaction consumer as variable mediation.